Negative empathy: History, theory, criticism - Ercolino, Stefano (Orbis litterarum, 2018)
Since its early formulation by Theodor Lipps, the concept of “negative empathy” has rarely received the attention it deserves in the scholarly debate on empathy. The present paper is an attempt to reconstruct its rough history and to propose a theory of negative empathy that is able to highlight its heuristic potential for the purpose of literary analysis, particularly for the study of the representation of the negative in literature. Drawing upon a range of fields of study, from neuroscience, psychology and psychonalysis to literary hermeneutics, cognitive literary studies, and aesthetics, I will try to lay the foundations for a reconceptualization of negative empathy. A high‐level form of empathy, negative empathy will be described, with relation to literature, as a potentially regressive aesthetic experience, consisting in a cathartic identification with negative characters, which can be either open to agency (indifferently leading either to pro‐ or antisocial behavior), or limited to the inner life of the empathizing subject. Such theoretical hypothesis will finally be tested on Jonathan Littell's novel The Kindly Ones .